IgA subclasses have different effector functions associated with distinct glycosylation profiles - Ulrike Steffen (Nature Portfolio, 2020)
Immunoglobulin A (IgA) has two subclasses, IgA1 and IgA2, but differential effects on inflammation are unclear. Here the authors show that IgA2, when compared with IgA1, has stronger pro-inflammatory functions associated with changed glycosylation and higher disease scores in patients with rheumatoid arthritis.